2018
DOI: 10.1073/pnas.1806305115
|View full text |Cite
|
Sign up to set email alerts
|

Role of PDGF receptor-α during human cytomegalovirus entry into fibroblasts

Abstract: Human CMV (HCMV) exhibits a broad cell tropism that depends on two virion glycoprotein complexes: a trimeric complex (gH/gL/gO) that facilitates viral infection primarily in fibroblasts and a pentameric complex (gH/gL/pUL128-pUL130-pUL131A) that mediates infection in epithelial and endothelial cells. We performed genomewide CRISPR screens in which the PDGF receptor-α (PDGFRα) was identified as the most significant cellular gene product essential for infection by HCMV virions containing only trimeric complex (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 52 publications
2
103
0
Order By: Relevance
“…Multiple reports have monitored foci size in the presence of neutralizing antibodies and attributed the cell-associated nature of ME to the expression of the UL128-131 and RL13 loci (24, 42). It seems clear that either gH/gL/gO or gH/gL/UL128-131 is required for cell-associated spread on fibroblasts, whereas gH/gL/UL128-131 seems to be required for cell-associated spread in epithelial or endothelial cells (24, 26, 43, 44). Moreover, the pathway of cell-associated spread for HCMV has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple reports have monitored foci size in the presence of neutralizing antibodies and attributed the cell-associated nature of ME to the expression of the UL128-131 and RL13 loci (24, 42). It seems clear that either gH/gL/gO or gH/gL/UL128-131 is required for cell-associated spread on fibroblasts, whereas gH/gL/UL128-131 seems to be required for cell-associated spread in epithelial or endothelial cells (24, 26, 43, 44). Moreover, the pathway of cell-associated spread for HCMV has not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that PDGFRα specifically interacts with the gO subunit of the trimer which is required for entry into fibroblasts (2528). As soluble forms of PDGFRα or derivatives thereof can inhibit cell-free infection of several cell types (26) it appears that binding of sPDGFRα to gO interferes with trimer-mediated function(s) widely required for cell entry.…”
Section: Discussionmentioning
confidence: 99%
“…One of these cellular receptors, platelet-derived growth factor receptor alpha (PDGFRα), was identified to directly and specifically interact with gO parts of the trimer (2527). This interaction enables entry of cell-free virions into fibroblasts, the only cell type which shows a high PDGFRα expression (28). Albeit, soluble forms of PDGFRα (sPDGFRα) can severely inhibit not only entry into fibroblasts, but also entry into endothelial and epithelial cells (2527), and first observations indicate that the inhibitory capacity of sPDGFRα is effective against several HCMV strains even when they harbour a different gO genotype sequence (26).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, UL148 appears to stabilize immature forms of glycoprotein O (gO) within the ER, thereby promoting the maturation and incorporation into virions of the heterotrimeric glycoprotein H (gH)/ glycoprotein L (gL)/ gO complex. Since gH/gL/gO is one of the two alternative gH/gL complexes that endow virus with the ability to utilize specific host cell surface receptors during entry, in this case with gO being required to achieve cell entry via PDGFR α , which is well expressed in fibroblasts but poorly expressed in epithelial cells (1922), the effects of UL148 on trimer expression are thought to account for the ∼100-fold improved replication of UL148 -null viruses in epithelial cells (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…gH/gL/gO (Trimer) and gH/gL/UL128-131 (Pentamer) are the two alternative HCMV gH/gL complexes that endow the virus with the ability to utilize different proteinaceous host cell surface factors as entry receptors [reviewed in (19)]. In particular, gO, in the context of Trimer, is required for viral entry via the platelet-derived growth factor receptor alpha (PDGFR α ), which is well expressed in fibroblasts but poorly if at all in epithelial cells (2023). Infection of epithelial and endothelial cells, on the other hand, appears to require direct interactions between the Pentamer and neuropilin-2 (Nrp2) (24), together with roles for OR14I1 (25) and CD147 (26), addition to roles for the Trimer (27, 28).…”
Section: Introductionmentioning
confidence: 99%